2008
DOI: 10.3174/ajnr.a0829
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Therapy of Symptomatic Intracranial Stenosis in Patients With Impaired Regional Cerebral Blood Flow or Failure of Medical Therapy

Abstract: BACKGROUND AND PURPOSE: Symptomatic intracranial stenoses have a high risk for a recurrent stroke if treated medically. Although angioplasty and stent placement are proposed treatment options, data on longer-term outcome are limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…All three were continued on dual antiplatelet therapy. Re-stenosis rates were consistent with previously reported rates of 27–35% 20 21…”
Section: Discussionsupporting
confidence: 92%
“…All three were continued on dual antiplatelet therapy. Re-stenosis rates were consistent with previously reported rates of 27–35% 20 21…”
Section: Discussionsupporting
confidence: 92%
“…In series with angiographic followup, the restenosis rate was cited to be within the range of 7.5% and 35% [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, rescue angioplasty with or without stenting may prevent reocclusion in a stenotic artery and permit distal infusion of thrombolytic agents [9]. In addition, mechanical disruption of an occlusive thrombus using a mechanical retrieval device or balloon angioplasty may fragment the thrombus and present a greater surface area for thrombolytic agent binding and may improve the effi cacy of chemical thrombolysis [14].…”
Section: Indicationsmentioning
confidence: 99%
“…The rate of stroke and death from intracranial angioplasty and stenting is 9.5% [12]. The rate of restenosis is 32.4% to 35%, of which 50% become symptomatic [13,14]. The option of conventional surgical intervention fell into disfavor following the EC/IC bypass study, which demonstrated no advantage for EC-IC bypass and greater rates of fatal and non-fatal strokes [15].…”
Section: Introductionmentioning
confidence: 99%